Time-dependent effect of an oral hypoglycemic agent upon serum glucose levels - Gagliardino, Juan José (1973)
A constant dosage of glibenclamide (50 µg/kg i.p.) was administered to normal mice at 4-h intervals during the day. Blood samples were collected up to 360 min after the injection, for glucose determination. It was found that neither the depth nor the duration of the glibenclamide-induced hypoglycemia was constant throughout the day. These results demonstrate the existence of a circadian rhythm of the glibenclamide effect on serum glucose levels. They also suggest that a day-time schedule of therapy with this drug should result in improved control of serum glucose.